Effect of Perceived Social Support Components on Happiness of Physical Veterans' Wives in Zanjan, Iran - N. Shams; M. Payami Bousari; A. Heyadari Some; R. Fallah (Afarand Scholarly Publishing Institute, 2020)
Aims: This study investigated the effect of perceived social support on the happiness of the wives of Zanjan physical veterans. Instruments & Methods: This is a descriptive correlational study. 188 wives of physical veterans with a percentage of 40% and above were selected by simple random sampling. Data were collected through Oxford and Zimet questionnaires and analyzed by multivariate regression in SPSS 25 software. Findings: The age group of 45 to 54 years, with 60.6%, had the highest frequency. 55.9% of veteranschr('39') wives' happiness level was high, 41% moderate, and 3.2% low. Among the happiness components, the lowest mean was related to the aesthetic (1.85) and the highest to self-efficacy (2.27). 78.72% of veteranschr('39') wives reported high perceived social support, 15.50% moderate, and 5.85% low. The highest averages were obtained from family (4.02), community (3.92), and friends (2.91), respectively. There was a significant relationship between the components of happiness and perceived social support (p<0.05). The results showed that the correlation coefficient of social support components with happiness (MR=0.443 and RS=0.96) was significant (p<0.00), and 19.6% of the variance of happiness is explained by the dimensions of perceived social support Among the three types of social support, only family support was predictive of happiness (p<0.00). Conclusion: Family support plays a major role in the happiness of physical veterans' wives.